An evaluation of muslim scholastic theology and human change: the perspective of Shaykh Mohammad Ghazali (1917-1996) - Bensaid, Benouda (2011)

(untitled)
This study examines the critical approach utilized by Shaykh Ghazali in his examination of the depth of impact of Muslim beliefs on human change; with particular focus on the means used by the Muslim faith to ensure the sustainment of a holistic undertaking of life, while nurturing a balanced interaction between human nature and reason without overlooking essential human freedoms or universal laws. In order to acquire a thorough understanding of such an issue, this study sheds light on Ghazali’s perspective regarding the development of Muslim scholastic theology, and its consequent ramifications on the shaping of Muslim life as we know it today; in addition to soundly establishing a mode of reform that is critically required in both the teaching and instruction of Muslim theology in the present day. Ghazali’s perspective on the reformation of Muslim theology stands on the brink of forging a new religious and intellectual identity, alongside a focused, driven social orientation for contemporary Muslim societies. His contribution however, is vital to the current debate on Islam, development and modernity, for the distinct reason that it addresses vitally critical problems pertaining to religious faith, its practice, and the social culture of Muslims in modern times.